EXAFS wavelet transform analysis of Cu-MOR zeolites for the direct methane to methanol conversion. Issue 34 (24th June 2020) - Martini, Andrea; Signorile, Matteo; Negri, Chiara; Kvande, Karoline; Lomachenko, Kirill A.; Svelle, Stian; Beato, Pablo; Berlier, Gloria; Borfecchia, Elisa; Bordiga, Silvia
Abstract : An innovative approach in EXAFS analysis and fitting using wavelet transforms reveals local structure and nuclearity of Cu-species in zeolites. Abstract : Cu-exchanged zeolites have been shown to possess Cu-oxo species active towards the direct methane to methanol (DMTM) conversion, carried out through a chemical-looping approach. Different Cu-zeolites have been investigated for the DMTM process, with Cu-mordenite (Cu-MOR) being among the most active. In this context, an accurate determination of the local structure and nuclearity of selective Cu-oxo species responsible for an efficient DMTM conversion still represents an ongoing challenge for characterization methods, including synchrotron-based X-ray absorption spectroscopy (XAS). Herein, we explore the potential of an alternative analysis of Extended X-ray Absorption Fine Structure (EXAFS) data using wavelet transform (WT) to enhance the technique sensitivity to multimeric Cu species hosted in the MOR framework. Combining ex situ XAS measurements under model red-ox conditions with in situ data collected after the key steps of the DMTM process, we demonstrate how EXAFS-WT enables unambiguous detection of Cu–Cu scattering contributions from multimeric Cu-species. As also confirmed by complementary in situ IR spectroscopy results, these are observed to dynamically respond to the chemical environment over the different conditions probed. We finally report a proof-of-concept EXAFS fit using the WT representation, applied to the structural refinement of O2 -activated Cu-MOR. The fitting results reveal a Cu local coordination environment consistent with mono-(μ-oxo) di-copper cores, with Cu–Cu separation of ∼3.1 Å, paving the way to future applications and developments of the method in the field of Cu-zeolite research and beyond.